Analisis Materi Aswaja dalam Buku Akidah-Akhlak Perspektif Kurikulum Berbasis Cinta - Sinta Karlina Dewi; Maimun; Naidatus Syarifah (Kartika: Jurnal Studi Keislaman, 2026)
This study analyzes the alignment of Aswaja material (Asy'ariyah and Maturidiyah) in the Grade XI Aqidah Akhlak textbook of Madrasah Aliyah with the principles of a Love-Based Curriculum. This research employs a qualitative approach with library research. Data collection techniques were carried out through documentation studies, while data analysis used content analysis. The findings reveal that the Aswaja material is systematically organized and contains three main values of the Love-Based Curriculum. First, the value of love for God is reflected in the discussion of God's attributes, belief in His power, and the strengthening of spiritual relationships. Second, the value of religious moderation is the most dominant aspect, evident in the moderate position of Asy'ariyah and Maturidiyah in addressing the relationship between reason and revelation, as well as respecting differing theological views. Third, the material contributes to character formation by instilling responsibility, tolerance, and avoidance of religious extremism. However, the values of the Love-Based Curriculum in this material are still presented implicitly. This study concludes that the Aswaja material has a reasonably strong alignment with the Love-Based Curriculum, yet a teacher's role is essential to contextualize the material so that these values can be optimally internalized by students